INVITRO SKIN SENSITIZATION MODEL - RASHMI GADWAL (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to develop a new in vitro skin sensitization model for predicting skin sensitizing potential of chemicals. We used THP-1, a human monocyte cell line for the optimization of human cell line activation test (h-CLAT) and conducted an inter-laboratory study by advanced molecular techniques. Sensitizers such as dinitrochlorobenzene (DNCB) enhanced expression of CD80, CD86 and other markers, while irritants such as sodium dodecyl sulfate (SDS) and dimethyl sulfoxide (DMSO) did not augment expression on THP-1 cells. A synergistic effect was observed when DNCB was added simultaneously to a culture. By evaluating the expression patterns of CD40, CD54, CD80 and CD86, we could classify the chemicals as sensitizers or non-sensitizers. These data suggest that THP-1 cells are good model for screening contact sensitizers and CD80 could be a useful marker complementary to CD54, CD86 and IL-β.